2019
DOI: 10.1039/c9cp02656h
|View full text |Cite
|
Sign up to set email alerts
|

Unusual temperature-sensitive excimer fluorescence from discrete π–π dimer stacking of anthracene in a crystal

Abstract: An unusual blue shift in excimer fluorescence with increasing temperature was observed from a crystal with a discrete π–π anthracene dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…For compound 2 , about 20 nm red shift in its emission spectra was observed by lowering the temperature from 293 to 77 K (Figure c). This unusual thermosensitivity may be attributed to increased structural torsion at high temperature and decreased π–π stacking between organic molecules due to increased vibrational and rotational motions at higher temperature. It may also arise from increased RISC at higher temperature to a S 1 state slightly higher in energy than the T 1 state. In contrast, very little temperature dependence was detected in the emission spectra of the μ 2 -DC hybrid structures (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…For compound 2 , about 20 nm red shift in its emission spectra was observed by lowering the temperature from 293 to 77 K (Figure c). This unusual thermosensitivity may be attributed to increased structural torsion at high temperature and decreased π–π stacking between organic molecules due to increased vibrational and rotational motions at higher temperature. It may also arise from increased RISC at higher temperature to a S 1 state slightly higher in energy than the T 1 state. In contrast, very little temperature dependence was detected in the emission spectra of the μ 2 -DC hybrid structures (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of NMR spectra and MD simulations we conclude that two molecules of AN are held within OA in a slipped-sandwich arrangement. Most likely such an arrangement is favored by π–π stacking between two AN molecules (distance 3.26 Å; Figure b). , Inclusion of AN within OA is probably facilitated by π–π interactions between AN molecules and the aromatic walls of the capsule (3.5 Å) and hydrophobic effecst due to the aqueous exterior. A perusal of Figure a also reveals the lack of free space around the AN molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In general, several approaches have been employed to enhance excimer emission from aromatic molecules. In crystals of aromatic molecules excimer emission is enhanced by controlling the interplanar π–π distance , between two molecules through pressure and temperature. , In solution this is achieved by covalently linking the two aromatic molecules that are involved in excimer formation . While this strategy is effective, one should note that upon functionalization one is no longer dealing with the parent system.…”
Section: Introductionmentioning
confidence: 99%
“…With suitable substituents, a columnar stacking of the fluorophores was avoided, and the anthracene dimers could be isolated from neighboring pairs. [132][133][134][135] The face-to-face interactions between the fluorophores are the dominant interaction resulting in an excimer formation. It was postulated that the absence of further interactions involving the fluorophore is beneficial to achieve higher emission efficiencies.…”
Section: Current Research Related To Anthracene Excimersmentioning
confidence: 99%
“…It was postulated that the absence of further interactions involving the fluorophore is beneficial to achieve higher emission efficiencies. [132][133][134][135] From recent examples, it can be concluded that substitution of the anthracene fluorophore on one side with a bulky substituent can induce the dimeric stacking motif. A twisted conformation of the substituent is beneficial for prohibiting a columnar stacking and for obtaining excimer emission.…”
Section: Current Research Related To Anthracene Excimersmentioning
confidence: 99%